Policy Mix and the US Trade Balance - Osorio Buitron, Carolina (IMF Working Papers; Working Paper ;, 2017)
The strong US policy response to the 2008-09 financial crisis raised concerns about its impact (spillovers) on other countries, with great focus on the monetary stimulus but little attention to fiscal policy, despite their combined deployment. Using a sign-restricted structural VAR approach, we study the trade spillovers of the post-crisis policy mix, by assessing the joint impact of monetary and fiscal policy. We find that aggregate trade effects, as reflected in the trade balance, varied across time, reflecting the different timing of fiscal and monetary stimuli, with overall positive spillovers in the immediate aftermath of the crisis. At the same time, reflecting the different transmission mechanisms of monetary policy, we find that the effects differed greatly between trading partners with fixed and flexible exchange rates. In general, our results highlight (i) the importance of studying fiscal and monetary policy spillovers jointly in order to avoid attenuation bias from omitted variables; and (ii) that trading partners' exchange rate regimes are of first order importance in determining the impact of policy spillovers.